Damping of periodic bending structures featuring nonlinearly interfaced piezoelectric elements. (October 2016) - Lallart, Mickaël; Yan, Linjuan; Richard, Claude; Guyomar, Daniel
This paper presents the combination of periodic structures with nonlinearly interfaced piezoelectric elements for vibration control purposes. The nonlinear treatment consists of quickly inverting the piezoelectric voltage when the latter reaches either a maximum or a minimum value, hence shaping a voltage with a higher magnitude and reduced phase with the speed. It is shown that the nonlinear interface not only dramatically increases the damping abilities of periodic structures in stopband, but also permits significantly enlarging the latter, hence providing a very adaptive, efficient vibration damping system. Theoretical and experimental investigations on a clamped–clamped periodic beam are conducted, showing the very good abilities for efficiently damping the mechanical vibrations over a very wide frequency band.